The beta‐isoform of the BRCA2 and CDKN1A(p21)‐interacting protein (BCCIP) stabilizes nuclear RPL23/uL14. Issue 20 (19th August 2014) - Wyler, Emanuel; Wandrey, Franziska; Badertscher, Lukas; Montellese, Christian; Alper, Daniel; Kutay, Ulrike
Abstract : BRCA2 and CDKN1A(p21, CIP1)‐interacting protein (BCCIP) is an evolutionary conserved protein implicated in maintenance of genome stability and cell cycle progression. Two isoforms of BCCIP with distinct C‐terminal domains exist in humans. We show that mammalian BCCIPβ, but not BCCIPα, forms a ternary complex with the ribosomal protein RPL23/uL14 and the pre‐60S trans‐acting factor eIF6. Complex formation is dependent on an intact C‐terminal domain of BCCIPβ. Depletion of BCCIPβ reduces the pool of free RPL23, and decreases eIF6 levels in nucleoli. Overexpression of BCCIPβ leads to nucleoplasmic accumulation of extra‐ribosomal RPL23 and stabilizes overexpressed RPL23, suggesting that BCCIPβ functions as nuclear chaperone for RPL23. Abstract : Human BCCIPβ forms a protein complex with RPL23 and eIF6 in vivo and in vitro . Complex formation requires an intact C terminus of BCCIPβ. Overexpression of BCCIPβ leads to nucleoplasmic accumulation of RPL23. BCCIPβ stabilizes extra‐ribosomal RPL23.